Spatio-temporal distribution pattern of Calanus sinicus and its relationship with climate variability in the northern Yellow Sea. (17th August 2017) - Yang, Qing; Liu, Hui; Liu, Guize; Gu, Yanbin; ,
Abstract: The spatio-temporal distribution pattern of Calanus sinicus, a key copepod species, was examined in the northern Yellow Sea (YS). Compared with 1959 and 1982, there was a significant increase in the abundance of C. sinicus in the spring, summer, and autumn of 2011 and winter of 2014. The percentage of C. sinicus in the zooplankton assemblages ranging from 45.6 to 75.8% in different seasons of 2011-2014 was significantly higher than that in 1982. Two different spatial distribution patterns of C. sinicus were observed, with higher abundance occurring nearshore during the cold season (e.g. January) and offshore in the central portion of the northern YS in the warm season (e.g. May, July, and October). The YS Cold Water Mass in the central portion of the northern YS likely provides an important over-summering site for the species. Additionally, a greater increase of the abundance of C. sinicus was found in the northern portion (the northern YS) of its spatial distribution during the past half century. This study has an implication on the climate-driven shifts in zooplankton community in the northern YS, highlighting the importance of C. sinicus in the warm-temperate ecosystem of Chinese coastal seas.